IMPORTED FIBULAE FROM THE KAMA REGION OF THE FIRST CENTURIES AD: MECHANISMS AND ROUTES OF RECEIPT - Krasnopeorov A.A. (Вестник Брянского государственного университета)
The article summarizes the study of “imported” fibulae in the Kama region, the early («Sarmatian») period of their distribution. The purpose of this publication is to discuss the ways and mechanisms of the appearance of fibulae in the Kama region. The typological spectrum of fibulae allows us to distinguish 3 stages of their distribution, which also differ geographically. 1st – fibulae of groups Almgren-242, Almgren-87, Almgren-204, or I-II centuries. AD; 2nd – fibulae of the group Almgren-156 and enameled brooches, or 1 half of the 3rd century; 3rd – fibulae of the Almgren-192, or 2 half of the III – beginning (?) IV centuries. The types of fibulae of the third period are completely oriented towards the Sarmatian groups of the southern Urals. The second period reflects the time of formation of the Mazunino and Azelino cultures. Cartography of fibulae of the «1st period of circulation» does not allow us to consider the «Sarmatian» steppe zone as the source or channel of their distribution. In this case, the «Western path» is likely, as evidenced by other circumstances. The vector of influx of fibulae is as follows: Kama region <– Oka (Sura) <– upper and middle Don region <– «Black Sea region». The events are not homogeneous in time, and are associated with (a) the collapse of the Zarubintsy culture, (b) the formation of 1 horizon (Rakhny-Lyutezh-Pochep) of the late Zarubintsy monuments, (c) the advance of the Zarubintsy and late Zarubintsy groups to the east and north (to the Dyakovo area), (d) «wars of the 1st century». It is with this wave (and not directly with the Sarmatians) – «the Zarubinets» / «Late Zarubinets» / «Andreevka-Piseraly», mixed with the Upper Don post-Late Scythian – that the appearance of part of the «Sarmatian» elements in the Pyany Bor monuments is associated. Including the distribution of fibulae of the groups Almgren-242, Almgren-87, Almgren-204.